SPATIAL MODELING FOR MARICULTURE SITE SELECTION BASED ON ECOSYSTEM PARAMETERS AT KUPANG BAY, EAST NUSA TENGGARA INDONESIA - Agus Hartoko; A.L. Kangkan (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2009)
The aims of the study were : a. to identify the physical, chemical and biological parameters at the utilization zone-coastal water of Kupang Bay, East Nusa Tenggara, b. to analyze the value of coastal water suitability from the physical, chemical and biological parameters for the development for maniculture at the utilization zone of Kupang Bay, East Nusa Tenggara, c. to select the sub zone for the sea weed culture, grouper fish culture site using the system of floating net cage and the culture of pearl oyster. The method used in the study is a spatial approach by conducting the direct measurement of the physical, chemical, and biological parameters. Mapping and spatial model was processed and analyzed through a geo-statistic method. The site selection for mariculture sub-zones were constructed through a spatial scoring and spatial interaction-RGB model and based on matrix of ecosystem parameters suitability score and weighting. With consideration that any numerical, mathematical or spatial model related to the surface of the earth or an ecosystem should take into account the concept of 4D function of its spatian distribution (x,y,z)and temporal consideration (time) such as seasonal data. The result showed that the range values of the physical, chemical, and biological parameters at utilization zone of the Kupang Bay are as follow: 1. Variable of physical parameters were: a). depth 5-25 m, b). transparancy 3.00-11.00 m, c). temperature 26-28.45 degree of celcius, d). salinity 31.50-38.20 ppt, e). substrate consist of: sand, sandy clay, clay sand, silt clay, silt, sand, and coral, f). current velocity 0.059-0.238m per s, and g). total suspended solid 180-305mg per l. 2. Variable of chemical parameters were: a). dissolved oxygen 6.85-8.74 ppm, b). pH 7.97-8.59, c). phosphate is 0.081-0.435mg per l, and d). nitrate 0.145-4.134 mg per l, 3. Variable of biological parameter were: a). abundance of phytoplankton 106,760-210,380 cell per l, and b). chlorophyll-a 0.033-0.037 mg per m. Sub zone for seaweed culture identified mainly almost at all area of the middle of the Kupang Bay width about 7,544 hectares. The most-suitable sub-zone for grouper fish culture was 2,803 hectares wide and width of 1,336 hectare of moderately-suitable. Sub zone for pearl culture exist especially at the north part of Kupang Bay and at some area nearby at the mouth of the Kupang Bay wide about 4.383.8 hectares. The approach with the above concept had proved that with a significance difference of scoring-weight on each specific and important ecosystem parameters for each spatial analysis purposes (i.e.50 percent scoring-weight of nitrate and phosphate for sea weed culture sub zone; 40 percent scoring-weight of dissolved oxygen for fish culture sub zone and 40 percent scoring weight of plankton abudance for oyster pearl culture sub zone), had resulted in a distinctive and specific delineation for each culture sub zones, thus avoiding and less on sub zonal overlapping. Keywords: Ecosystem parameters, Kupang Bay, Mariculture, Spatial model.